IMPLEMENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING DALAM PEMBELAJARAN IPA DI KELAS VII UPT SMP 032 KARYA KECAMATAN PAKKAT, KABUPATEN HUMBANG HASUNDUTAN T.A. 2025/2026 - Elsina Sihombing; Siskawati Panjaitan; Rajiman Simanullang; Alex Bob Siringoringo; Rumondang Bellania Sibarani; Nikita Sibarani; Leli Dame Marisa Pardede (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of the Discovery Learning model in science learning for seventh-grade students at UPT SMP 032 Karya, Pakkat District, Humbang Hasundutan Regency, Academic Year 2025/2026. This research employed a qualitative approach with a descriptive research type. The research subjects consisted of science teachers and seventh-grade students. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study showed that the implementation of the Discovery Learning model in science learning was carried out through the stages of stimulation, problem statement, data collection, data processing, verification, and generalization. The application of this learning model was able to increase students’ activity and involvement in the learning process. Students became more active in asking questions, participating in discussions, and expressing opinions during the learning activities. In addition, the teacher acted as a facilitator, motivator, and guide in helping students discover learning concepts independently. However, the implementation of Discovery Learning still faced several obstacles, such as limited learning time, inadequate learning facilities, and the presence of students who were still less active in group discussions. To overcome these obstacles, the teacher made various efforts such as providing learning motivation, guiding students directly, managing the classroom effectively, and utilizing simple learning media. Therefore, the implementation of the Discovery Learning model was able to create a more active, interesting, and meaningful science learning process for students